Imaging of grain-level orientation and strain in thicker metallic polycrystals by high energy transmission micro-beam Laue (HETL) diffraction techniques - Hofmann, F; Abbey, B; Connor, L; Baimpas, N; Song, X; Keegan, S; Korsunsky, A (2012)
For high performance, safety-critical applications, such as aerospace components, in-depth understanding of the material's response to complex loading conditions is essential. Moreover, it is vital to know how the material behaviour may be modified as a consequence of fatigue loading and how its eventual failure occurs. Unlike bulk properties, such as stiffness, yield stress, etc. that depend on the average response of the grains in a polycrystal, material failure is determined by "weakest link" type mechanisms. These depend strongly on grain-level deformation behaviour and grain-to-grain interactions. Micro-beam Laue diffraction is a powerful tool to probe these phenomena. However, the classical setup is limited to the study of sample surface regions or thin sections, due to the limited penetration into the sample at photon energies of 5 - 25 keV. A much more useful tool for the material scientist and engineer would allow the probing of grain-level orientation and stress in thicker sections of engineering components. To this end, we have developed the high energy transmission Laue (HETL) technique, an extension of the micro-beam Laue technique to significantly higher photon energies (50 - 150 keV). For the imaging of lattice orientation and elastic strain in three dimensions, we propose two alternative approaches: Laue orientation tomography (LOT) and high energy differential aperture X-ray microscopy (HEDAXM). In this paper an overview of the recent progress in HETL, LOT and HEDAXM measurements will be given and some first results illustrating the potential of these techniques presented. © Carl Hanser Verlag GmbH andCo. KG.